Adaptive audio digital watermark algorithm based on m-sequence modulation - Wang, Hong; Ling Lu; Dashun Que; Junbo Huang (2004 7th International Conference on Signal Processing : proceedings : ICSP'04 : Aug. 31-Sept 4, 2004, Beijing, China, 2004)
This paper presents an adaptive audio digital watermark algorithm based on m-sequence modulation. Firstly, the visually recognizable binary watermark image should be converted into the one-dimensional sequence by the algorithm. The sequence is permuted pseudo-randomly and is modulated by m-sequence. Then the digital audio signal is set into segments and the discrete wavelet transform is performed. Finally the modulated signal is embedded in the coefficients with relatively large absolute value on middle frequency range detail signal adoptively. The experimental results show that the watermark is imperceptible and the algorithm is robust to digital audio signal when attacked by low pass filter, re-quantified and so on.